2002
DOI: 10.1074/jbc.m112053200
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the Small Plastid-encoded PsbJ Polypeptide Results in a Defective Water-splitting Apparatus of Photosystem II, Reduced Photosystem I Levels, and Hypersensitivity to Light

Abstract: Photosystem II is a large pigment-protein complex catalyzing water oxidation and initiating electron transfer processes across the thylakoid membrane. In addition to large protein subunits, many of which bind redox cofactors, photosystem II particles contain a number of low molecular weight polypeptides whose function is only poorly defined. Here we have investigated the function of one of the smallest polypeptides in photosystem II, PsbJ. Using a reverse genetics approach, we have inactivated the psbJ gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 54 publications
6
37
2
1
Order By: Relevance
“…Transplastomic tobacco plants that have a mutation in PsbE showed lower associations between PsbP and PSII in the thylakoid membranes (45). It was reported that PsbJ in the vicinity of Cyt b 559 is required for the association of PsbP with PSII and the assembly of PsbR in tobacco (35,46), and that PsbR is required for the stable binding of PsbP and PsbQ in Arabidopsis (36). In addition, we observed a putative cross-linking between PsbR and PsbE (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Transplastomic tobacco plants that have a mutation in PsbE showed lower associations between PsbP and PSII in the thylakoid membranes (45). It was reported that PsbJ in the vicinity of Cyt b 559 is required for the association of PsbP with PSII and the assembly of PsbR in tobacco (35,46), and that PsbR is required for the stable binding of PsbP and PsbQ in Arabidopsis (36). In addition, we observed a putative cross-linking between PsbR and PsbE (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, another LMM protein PsbJ is, in turn, required for the assembly of the PsbR protein, thus explaining the earlier reported importance of PsbJ for the assembly of PsbP (11,12). An interesting adaptation to constant low light conditions was detected; in WT plants, the OEC proteins PsbP and PsbQ as well as PsbR were up-regulated, whereas the PsbO amounts were not dependent on light intensity.…”
Section: Peculiar Regulation Of the Oec Proteins And The Psbr Proteinmentioning
confidence: 63%
“…The 23-and 17-kDa OEC proteins PsbP and PsbQ have been found to associate with PSII only in the grana thylakoids (9). Moreover, the low molecular mass (LMM) PSII core protein PsbJ was recently reported to be a prerequisite for the association of PsbP with the PSII core (11,12). It has been suggested that PsbO provides a docking site for PsbP, and both PsbO and PsbP together are needed for the binding of PsbQ (13,14).…”
Section: Photosystem II (Psii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Además, previamente se ha informado que un deterioro o una promoción en el proceso de escisión del agua en el PSII deberían notarse en el rendimiento de la fluorescencia. Por ejemplo, en plantas mutantes de tabaco que carecen de un polipéptido específico en su aparato de escisión de agua en el PSII, exhiben valores de fluorescencia mínima (F 0 ) más altos y de fluorescencia variable (Fv) casi equivalentes a cero (Hager, Hermann, Biehler, Krieger-Liszkay, & Bock, 2002). Dado que no se observaron diferencias significativas entre el control y las plantas tratadas en los parámetros de fluorescencia, este estudio sugiere que el ATM no es metabólicamente susceptible a una división diferencial en el complejo oxidante del H2O.…”
Section: Parámetros De Fluorescenciaunclassified